2021
DOI: 10.1097/eja.0000000000001618
|View full text |Cite
|
Sign up to set email alerts
|

Associations between different measures of intra-operative tachycardia during noncardiac surgery and adverse postoperative outcomes

Abstract: BACKGROUND Intra-operative tachycardia during noncardiac surgery has been associated with adverse postoperative outcomes. However, harm thresholds for tachycardia have not been uniformly defined. The definition of intraoperative tachycardia that best correlates with adverse postoperative outcomes remains unclear.OBJECTIVE We aimed to identify the definition of intraoperative tachycardia during noncardiac surgery that is associated with the best predictive ability for adverse postoperative outcomes.DESIGN A sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
(134 reference statements)
1
9
0
Order By: Relevance
“…However, we noticed that the injury was apparent when the intraoperative HR exceeded 115 bpm (aOR, 2.55 [95% CI: 1.06–6.12]). Furthermore, the threshold for tachycardia gradually decreased as the cumulative duration increased in our study, consistent with the results of previous observational studies ( 24 , 36 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we noticed that the injury was apparent when the intraoperative HR exceeded 115 bpm (aOR, 2.55 [95% CI: 1.06–6.12]). Furthermore, the threshold for tachycardia gradually decreased as the cumulative duration increased in our study, consistent with the results of previous observational studies ( 24 , 36 ).…”
Section: Discussionsupporting
confidence: 93%
“…Troponin elevation has also been strongly associated with higher morbidity and 30-day mortality ( 17 20 ). Previous studies ( 21 24 ) have reported the perioperative risk factors of myocardial injury after non-cardiac surgeries. In addition to intraoperative heart rate (HR) and blood pressure (BP), patient characteristics are also associated ( 16 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…47 In a cohort of adult patients undergoing surgery under general anesthesia, patients whose heart rates were greater than or equal to 100 beats per minute for 30 minutes or longer had a 2.1-fold increase in mortality within 30 days of surgery compared with those who did not experience this tachycardia; a heart rate of greater than or equal to 120 beats per minute for five minutes or longer produced a 50% increase in mortality. 47 Intraoperative hypotension and tachycardia appear to have an additive effect on the risk of AMI. 48 These and similar findings have led to a PeriOperative Quality Initiative consensus statement recommendation on perioperative BP management.…”
Section: Hemodynamic Instabilitymentioning
confidence: 99%
“…Bradycardia was de ned as a 5-minute average HR decreasing to < 60 bpm or the administration of anticholinergic medications, such as atropine or glycopyrrolate [26]. Tachycardia was de ned as an average HR > 120 bpm or the use of esmolol to decrease HR [27]. Hypoxemia was de ned as SpO 2 < 95%, and severe hypoxemia as SpO 2 < 90% [28].…”
Section: Study Design Sample and Data Collectionmentioning
confidence: 99%